Strategy To Improve The Performance Of Sustainable Palm Oil Suppliers at PT. Nusantara III Plantation - Saqdiah, Fatma; Mulya, Diki Akhwan; Naldi, Syafri; Nursamsi, Nursamsi (Riwayat: Educational Journal of History and Humanities, 2025)
Supply chain sustainability in the palm oil industry is an important aspect in maintaining the efficiency and competitiveness of the company. This study aims to analyze the strategy of improving the performance of palm oil suppliers in PT. Nusantara III Plantation, especially in the Hapesong PKS. The research method used is SWOT analysis with the Internal Factor Evaluation Matrix (IFE) and External Factor Evaluation Matrix (EFE) approaches. The results of the study show that the main strength factor of Hapesong PKS is the ownership of sustainability certifications (ISPO and RSPO) and a good occupational safety management system. However, there are obstacles in the quality of raw materials from partner suppliers as well as price competition with competitors. Based on the SWOT analysis, the recommended strategies include facilitating ISPO certification for suppliers, developing cooperation with new suppliers, collaborating with the government in sustainability socialization, and implementing a reward and punishment system for suppliers. The implementation of this strategy is expected to improve supplier performance and strengthen the sustainability of the supply chain at the Hapesong PKS.